Selection of acid salts: a critical step in creating an acidic condition for plasma iron release and measurement - Lim, Wai Feng; Abdullah, Maha; Ho, Kok Lian; Yap, Boon Kar; Lai, Mei I. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Iron deficiency anaemia (IDA) is the most common cause of anaemia worldwide. Determination of body iron status is necessary to diagnose IDA. This can be measured using a biochemistry assessment of the serum/ plasma. Plasma/serum iron quantitation is also important in diagnosing iron overload disorders. However, iron studies are limited due to high cost and lack of access to biochemical analysers. Therefore, a cost- and technical-effective method is needed to measure human plasma iron concentration. Plasma iron is mainly transferrin-bound and an acidic plasmic condition is necessary to release the iron. This study investigated various candidate acid salts to achieve the acidic condition needed for plasma iron release. Method: Ten powdered or crystallised acid salts were studied for their water solubility as well as their pH reduction capability in revised simulated body fluid (r-SBF) and commercially available human plasma without any change in colour or form. Results: Six acid salts studied were discontinued from further investigation because they were insoluble in water. Another two candidates were unsuitable as they precipitated in r-SBF and human plasma. Maleic acid formed a jelly-like texture after a certain amount of time in human plasma. Only citric acid met all the criteria of a suitable acid salt to be investigated further as part of the reagent for a spontaneous plasma iron measurement. Conclusion: Citric acid, which is a colourless and odourless acid salt, was selected to lower the human plasma pH to an acidic condition for transferrin-bound iron release.